PENINGKATAN PERILAKU SOPAN SANTUN MELALUI METODE BERCERITA PADA ANAK USIA 5-6 TAHUN DI TK LKIA II PONTIANAK SELATAN - Beata Sagala, Hana Martica (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThis study aims to improve the behavior of courtesy through the method of telling the story of children aged 5-6 years in TK LKIA II South Pontianak. The form of this research is classroom action research with descriptive method. Research subjects were teachers amounting to 1 person and 15 children. Based on the results of research that has been done and through the results obtained after the analysis of data that 1) learning planning in improving the behavior of courtesy through the method of storytelling in children aged 5-6 years can be categorized "good", among others: create a plan of daily activities, Selection of play materials, selection of learning methods, problem formulation. 2) The implementation of learning in improving the behavior of courtesy through storytelling method in children aged 5-6 years can be categorized as "good", among others: determine the material and formulate goals, manage class interaction, demonstrate the ability in learning, carry out process assessment and learning outcomes , General impression of process and learning outcomes. 3) Improving the behavior of courtesy through the storytelling method to children aged 5-6 years: the child thanked when given the gift (gift) from the people, the child said the word help when receiving help from others, children learn patience to admit error. Based on the results of research that has been implemented then researchers can suggest to teachers in improving the behavior of courtesy in children, among others: Teachers can make learning planning by taking into account the basic competence standards, so that the implementation can be run systematically.Â Keywords: Sopan Santun, Method of Storytelling